COOPERATION BETWEEN THE UNESCO IITE AND UNESCO ASSOCIATED SCHOOLS - Nella M. Pruss (Высшее образование в России, 2016)
The article describes the main areas of cooperation between the UNESCO IITE and the UNESCO Associated Schools Project Network (ASPnet) on ICT in education. UNESCO IITE and the UNESCO ASPnet Pilot project «LFF - Learning For the Future» includes 42 associated schools from 14 UNESCO Member States, and its results have started an active dissemination among the Russian schools for establishment of partner communications and for implementation of joint educational and research projects.